Qualitative grading of aortic regurgitation: a pilot study comparing CMR 4D flow and echocardiography - Chelu, Raluca G. (Int J Cardiovasc Imaging, 2015)
Over the past 10 years there has been intense research in the development of volumetric visualization of intracardiac flow by cardiac magnetic resonance (CMR). This volumetric time resolved technique called CMR 4D flow imaging has several advantages over standard CMR. It offers anatomical, functional and flow information in a single free-breathing, ten-minute acquisition. However, the data obtained is large and its processing requires dedicated software. We evaluated a cloud-based application package that combines volumetric data correction and visualization of CMR 4D flow data, and assessed its accuracy for the detection and grading of aortic valve regurgitation using transthoracic echocardiography as reference. Between June 2014 and January 2015, patients planned for clinical CMR were consecutively approached to undergo the supplementary CMR 4D flow acquisition. Fifty four patients (median age 39 years, 32 males) were included. Detection and grading of the aortic valve regurgitation using CMR 4D flow imaging were evaluated against transthoracic echocardiography. The agreement between 4D flow CMR and transthoracic echocardiography for grading of aortic valve regurgitation was good (κ = 0.73). To identify relevant, more than mild aortic valve regurgitation, CMR 4D flow imaging had a sensitivity of 100 % and specificity of 98 %. Aortic regurgitation can be well visualized, in a similar manner as transthoracic echocardiography, when using CMR 4D flow imaging. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10554-015-0779-7) contains supplementary material, which is available to authorized users.